von Willebrand Factor is elevated in HIV patients with a history of thrombosis - van den Dries, Lennert W. J.; Gruters, Rob A.; Hövels–van der Borden, Sascha B. C.; Kruip, Marieke J. H. A.; de Maat, Moniek P. M.; van Gorp, Eric C. M.; van der Ende, Marchina E. (Frontiers in Microbiology, 2015)
Background Arterial and venous thrombotic events are more prevalent in HIV infected individuals compared to the general population, even in the era of combination antiretroviral therapy. Although the mechanism is not fully understood, recent evidence suggests a role for chronic immune activation. Methods We reviewed the Dutch National HIV registry database for HIV infected patients in Rotterdam with a history of arterial or venous thrombosis and calculated the incidence. We collected samples from patients with and without thrombosis to compare plasma levels of lipopolysaccharide (LPS), LPS binding protein (LBP), soluble CD14 (sCD14), and von Willebrand Factor antigen level (vWF). Results During a 10-year period, a total of 60 documented events in 14,026 person years of observation (PYO) occurred, resulting in an incidence rate of 2.50, 2.21 and 4.28 for arterial, venous and combined thrombotic events per 1000 PYO, respectively. The vWF was elevated in the majority of study subjects (mean 2,36 SD±0.88 IU/ml); we found a significant difference when comparing venous cases to controls (mean 2.68 SD±0.82 IU/ml vs 2.20 SD±0.77 IU/ml; p=0.024). This difference remained significant for recurrent events (mean 2.78 SD±0.75p=0,043).). sCD14 was positively correlated with LPS (r=0.255; p=0.01). Conclusion The incidence of venous thrombosis was twofold higher in HIV infected patients compared to age-adjusted data from general population cohort studies. We couldn't find a clear association between immune activation markers to either arterial or venous thrombotic events. We observed a marked increase in vWF levels and observed a correlation of vWF to first and recurrent venous thrombo-embolic events. These findings suggest that HIV infection is an independent risk factor for coagulation abnormalities and could contribute to the observed high incidence in venous thrombosis. This could be a reason to prolong anti-thrombotic treatment in HIV patients with a history of thrombosis.